2016
DOI: 10.1002/mus.25368
|View full text |Cite
|
Sign up to set email alerts
|

MR neurography for the evaluation of CIDP

Abstract: MR neurography and the measurement of peripheral nerve volume are useful for diagnosing and assessing CIDP. Muscle Nerve 55: 483-489, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 21 publications
(35 reference statements)
0
23
0
Order By: Relevance
“…Application of ultrasound scores can increase diagnostic sensitivity for CIDP compared with other chronic immune-mediated, 39 hereditary 40 or diabetic neuropathies. 41 MRI techniques that have been evaluated in CIDP include magnetic resonance neurography [42][43][44] and diffusion tensor imaging (DTI). [45][46][47] DTI-based fractional anisotropy (FA) values are significantly lower in the nerves of the upper and lower extremities in CIDP, with the largest differences in ulnar and sciatic nerves compared with those of controls.…”
Section: Neuroimagingmentioning
confidence: 99%
“…Application of ultrasound scores can increase diagnostic sensitivity for CIDP compared with other chronic immune-mediated, 39 hereditary 40 or diabetic neuropathies. 41 MRI techniques that have been evaluated in CIDP include magnetic resonance neurography [42][43][44] and diffusion tensor imaging (DTI). [45][46][47] DTI-based fractional anisotropy (FA) values are significantly lower in the nerves of the upper and lower extremities in CIDP, with the largest differences in ulnar and sciatic nerves compared with those of controls.…”
Section: Neuroimagingmentioning
confidence: 99%
“…We excluded reviews, spinal cord studies and animal or in vivo studies. Our review identified a total of 35 articles: 24 DTI studies and 11 diffusionweighted MR neurography studies [31][32][33][34][35][36][37][38][39][40][41] . The number of lumbar nerve DTI studies has sharply increased in recent years ( Fig.…”
Section: Trends In Clinical Mr Neuroimaging Of Lumbar Nervesmentioning
confidence: 99%
“…7 Quantitative sensory testing is useful in documenting sensory dysfunction in patients with polyneuropathy. 8 Magnetic resonance imaging (MRI) 9 and neuromuscular ultrasound 10 have also been shown to be helpful in the evaluation of patients with peripheral neuropathy. With the current advances in neurophysiologic, immunologic, and genetic testing in peripheral neuropathy, the use of nerve biopsy is now primarily limited to patients with possible vasculitic neuropathy, select patients with possible amyloid neuropathy, and atypical forms of chronic inflammatory demyelinating polyradiculoneuropathy (CIDP).…”
mentioning
confidence: 99%